Candidate Policy Ideas and Other Factors that Affect Election Results: A Case Study of Kwame Nkrumah University of Science and Technology - Andy Anim; John Obeng Addai; Ernest Osei Akuoko; Rebecca Hammond; Casey Esaa Sey (Journal of Social and Development Sciences, 2022)
Politics primarily focuses on decision-making and resource allocation. This resource allocation may emerge from political parties and candidates' policy proposals. Numerous studies have explored the impact of candidate policy proposals on election outcomes, but less attention has been paid to the impact of other factors. Using Kwame Nkrumah University of Science and Technology (KNUST) as a case study, the study examines the impact of candidate policy proposals and other factors such as ethnicity, gender, and party affiliation on election outcomes. Kwame Nkrumah University of Science and Technology (KNUST) is located in Kumasi, in the Ashanti Region of Ghana. The sample size of 255 people came from the Department of History and Political Studies and the Department of English, both of which are part of the Faculty of Social Sciences. The third and fourth-year students in these departments were given online Google-style questionnaires. In addition, journal, article, and book data were used to support the analysis. The majority of survey respondents stated that politicians' policy opinions have a considerable impact on elections, which was a significant conclusion. In order to provide equal opportunity for all, the laws governing gender discrimination and ethnic politics must be properly enforced and followed. Possession of a party card should not be a prerequisite for receiving benefits in the country. Everyone should have equal access to opportunities.